Grapevine Phyllosphere Community Analysis in Response to Elicitor Application against Powdery Mildew - Nerva, Luca (Microorganisms, 2019)
The reduction of antimicrobial treatments and mainly the application of environmentally friendly compounds, such as resistance elicitors, is an impelling challenge to undertake more sustainable agriculture. We performed this research to study the effectiveness of non-conventional compounds in reducing leaf fungal attack and to investigate whether they influence the grape phyllosphere. Pathogenicity tests were conducted on potted Vitis vinifera “Nebbiolo” and “Moscato” cultivars infected with the powdery mildew agent (Erysiphe necator) and treated with three elicitors. Differences in the foliar microbial community were then evaluated by community-level physiological profiling by using Biolog(TM) EcoPlates, high throughput sequencing of the Internal Transcribed Spacer (ITS) region, and RNA sequencing for the viral community. In both cultivars, all products were effective as they significantly reduced pathogen development. EcoPlate analysis and ITS sequencing showed that the microbial communities were not influenced by the alternative compound application, confirming their specific activity as plant defense elicitors. Nevertheless, “Moscato” plants were less susceptible to the disease and presented different phyllosphere composition, resulting in a richer viral community, when compared with the “Nebbiolo” plants. The observed effect on microbial communities pointed to the existence of distinct genotype-specific defense mechanisms independently of the elicitor application.